ANALISIS STRUKTUR KOMUNITAS MAKROALGA EKONOMIS PENTING DI PERAIRAN INTERTIDAL MANOKWARI, PAPUA BARAT - Hendrik Victor Ayhuan; Neviaty Putri Zamani; Dedi Soedharma (Jurnal Teknologi Perikanan dan Kelautan, 2017)
Macroalga in Manokwari area has higher species biodiversity, however this organism is very risk to environmentkondition change either nature or anthropogenic pressure. This study aimed to composition species of algae (clasification and identification) and community assemblage analysis of macroalgae species surrounding Manokwari coastal area. Collecting data was done during east season period (from June 2014 to September 2014) from two different main coastal areas, mainland and outland coastal area. Twenty eight macroalga species were identified and consisted taxonomically of three divisions, three classes, eleven orders, sixteen families, and nineteen genus. Three divisions of macroalga species were green alga (Chlorophyta), red alga (Rhodophyta), and brown alga (Phaeophyta), which each division comprised with 14 species, 8 species, and 6 species respectively. Total of density average of macroalga species in outland was higher than that of in mainland. Structure analysis of macroalga community in outland areas (Mansinam and Lemon) had higher biodiversity index than that of in mainland areas (Rendani, Pasir Putih, and Arfai). Evenness index in both mainland and outland areas were closed to 1, which meant individual of macroalga from each species distributed uniformly and there was no dominant macroalga species. While dominancy index in either mainland or outland reached closely to zero, which meant macroalga community were stable.